IMPLEMENTASI PENDEKATAN PBL DENGAN PENDEKATAN CRT UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA KELAS 3 PADA MATA PELAJARAN MATEMATIKA - Aprilia Sekar Kinasih; Aji Heru Muslim (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This study aims to analyze the implementation of the Problem Based Learning (PBL) learning model with the Culturally Responsive Teaching (CRT) approach in improving the activeness and learning achievement of third-grade elementary school students in mathematics. The background of this study is based on the low active participation of students in the mathematics learning process, as well as the need for learning strategies that are relevant to students' culture. This study uses a descriptive qualitative method with third-grade students as subjects. Data were obtained through observation, interviews, and documentation of learning outcomes. The results show that the application of PBL with CRT can increase student activeness through discussions, questions, and active participation in problem solving. In addition, students' mathematics learning achievement increased after the application of this model. These findings indicate that the combination of PBL and CRT is relevant to create contextual, meaningful, and enjoyable learning in elementary schools.